2018
DOI: 10.1111/pace.13543
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of moderate to severe tricuspid regurgitation after dual‐chamber pacemaker implantation

Abstract: Introduction The incidence and predictors of tricuspid regurgitation (TR) after permanent pacemaker (PM) implantations have not been well evaluated. We attempted to determine TR's natural course and predictors, especially focusing on the influence of atrial fibrillation (AF). Methods Data from 530 patients with dual‐chamber PMs were evaluated. The main study outcomes were moderate to severe TR and isolated TR (moderate to severe TR without other structural heart diseases [SHDs]) in follow‐up echocardiography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Atrial fibrillation was found to represent a risk factor for CIED-associated progression of TR [ 17 , 29 ]. In our univariate regression for progression of TR, atrial fibrillation and single ventricular pacing lead was found to be significantly associated with progression of TR.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation was found to represent a risk factor for CIED-associated progression of TR [ 17 , 29 ]. In our univariate regression for progression of TR, atrial fibrillation and single ventricular pacing lead was found to be significantly associated with progression of TR.…”
Section: Discussionmentioning
confidence: 99%
“…B: Landmark analysis of hospitalisations for heart failure in patients with followup beyond 12 months in patients with device-related TR vs patients without device-related TR. atrial fibrillation [19]. It is difficult to remove confounding from the assessment of the cause of TR as these associated comorbidities are likely contributors to the development of this complication.…”
Section: Predictors Of Cied-related Trmentioning
confidence: 99%
“…Another important issue addressed in the present study is tricuspid regurgitation induced by a right ventricular lead. LDTD is a well-known complication of CIED implantation occurring at a rate of 25% to 35% (21)(22)(23)(24)(25)(26), not infrequently being a direct indication for TLE (25)(26)(27). LDTD contributes to RA and RV enlargement and increases pulmonary arterial pressure, and what is important, it is associated with higher mortality in patients having CIED.…”
Section: Discussionmentioning
confidence: 99%
“…LDTD contributes to RA and RV enlargement and increases pulmonary arterial pressure, and what is important, it is associated with higher mortality in patients having CIED. Significant TR associated with the presence of right ventricular leads worsens long-term prognosis and is an independent risk factor for premature death (22)(23)(24). On the other hand, timely removal of the lead inducing valve dysfunction may result in valve improvement (Figure 3).…”
Section: Discussionmentioning
confidence: 99%